2007
DOI: 10.1593/neo.07229
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid- Paclitaxel: Antitumor Efficacy against CD44(+) Human Ovarian Carcinoma Xenografts

Abstract: Numerous human tumor types, including ovarian cancer, display a significant expression of the CD44 family of cell surface proteoglycans. To develop tumor-targeted drugs, we have initially evaluated whether the CD44 ligand hyaluronic acid (HA) could serve as a backbone for paclitaxel (TXL) prodrugs. HA-TXL was prepared by modification of previous techniques. The in vitro cytotoxicity of HA-TXL against the CD44(+) human ovarian carcinoma cell lines SKOV-3ip and NMP-1 could be significantly blocked by preincubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 41 publications
3
118
0
Order By: Relevance
“…40). However, this work is different from most prior studies, in that the other studies used high molecular weight hyaluronic acid (>75 kDa) as the drug carrier (28,(41)(42)(43). We chose to use the smaller molecular weight hyaluronic acid as our previous work showed that in the preclinical model an approximately 4-kDa dextran was able to accumulate in numerous metastatic lesions, but the 70-kDa dextran had a more limited penetration (5).…”
Section: Discussionmentioning
confidence: 99%
“…40). However, this work is different from most prior studies, in that the other studies used high molecular weight hyaluronic acid (>75 kDa) as the drug carrier (28,(41)(42)(43). We chose to use the smaller molecular weight hyaluronic acid as our previous work showed that in the preclinical model an approximately 4-kDa dextran was able to accumulate in numerous metastatic lesions, but the 70-kDa dextran had a more limited penetration (5).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic properties, such as circulation time and biodistribution, are influenced by incorporating the targeting and cellspecific uptake properties of HA onto large carriers. Cargos delivered to CD44 over-expressing cells include anti-cancer drugs: epirubicin, 14 doxorubicin, 37,38,41,69,70,71 paclitaxel, 28,29,62,63 and mitomycin c, 14,70 as well as agents such as siRNA, 72 iron oxide magnetic particles, 73 and DNA. 74 These studies are summarized in Tables 3 and 4. Several different methods have been used to improve the distribution of doxorubicin, which has significant cardiotoxicity as a free drug.…”
Section: C Hyaluronan In a Targeted Nanocarrier Systemmentioning
confidence: 99%
“…In brief, previous investigations in vitro showed that a taxol-HA bioconjugate was cytotoxic to a panel of tumor cell lines (breast, colon and ovarian) but not human fibroblasts [65]. Although there are relatively few in vivo studies that have evaluated the efficacy of HA bioconjugates, previous investigations with a paclitaxol-HA bioconjugate have shown that it inhibits tumor growth of RT-112/84 human transitional cell carcinomas in mice and increases the survival of mice that had been inoculated with the NMP-1 or SK-OV-3ip human ovarian carcinoma lines [66,67]. Similarly, a butyrate-HA bioconjugate was found to inhibit tumor growth and reduced lung metastasis in mice inoculated with LL3 murine lung carcinoma cells [68].…”
Section: Drug Deliverymentioning
confidence: 99%